2011
DOI: 10.3233/ies-2011-0401
|View full text |Cite
|
Sign up to set email alerts
|

Maximal power of trunk flexor and extensor muscles as a quantitative factor of low back pain

Abstract: Torque-velocity and power-velocity relationships, which determine the different indicators of muscle function, have some practical application during rehabilitation program. These relationships for trunk flexor and extensor muscles during isokinetic conditions have yet to be studied in chronic lower back pain patients in order to demonstrate that maximal power could be used as a quantitative factor for this population. Ten healthy male subjects and eleven chronic lower back pain male patients performed series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…T 0 and P max were significantly higher for the trunk extensor than for the flexor one ( p , 0.05), with no statistical difference for V 0 . These results are in accordance with those previously found in the literature (Ripamonti et al 2011). They can be explained by (i) the muscle atrophy and fatty involution observed in subjects with CLBP before rehabilitation programme (Revel 1995) and (ii) the inability for these patients to mobilise muscles and to use lumbopelvic articulation (mobility and proprioception) during trunk flexion and extension comparing to healthy subjects (Mayer et al 1994).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…T 0 and P max were significantly higher for the trunk extensor than for the flexor one ( p , 0.05), with no statistical difference for V 0 . These results are in accordance with those previously found in the literature (Ripamonti et al 2011). They can be explained by (i) the muscle atrophy and fatty involution observed in subjects with CLBP before rehabilitation programme (Revel 1995) and (ii) the inability for these patients to mobilise muscles and to use lumbopelvic articulation (mobility and proprioception) during trunk flexion and extension comparing to healthy subjects (Mayer et al 1994).…”
Section: Resultssupporting
confidence: 94%
“…Many studies have focused on quantifying trunk muscle quality in CLBP (Mayer et al 1994). Thus, the force -velocity and powervelocity relationships give us an interesting overview about each individual muscle properties (Ripamonti et al 2011), in particular for trunk and lower limbs.…”
Section: Introductionmentioning
confidence: 99%
“…The load varies according to the velocity used during isokinetic testing. Ripamonti et al 23) demonstrated the importance of torque-velocity relationship during any rehabilitation program. Researchers had their measurements on a group of low back pain patients.…”
Section: Discussionmentioning
confidence: 99%
“…For each selected velocity, only the trial presenting the highest peak torque was considered for the data analysis. Maximal isometric torque (T 0 ), maximal velocity (V 0 ) and maximal power (P max ) were then extrapolated from the torquevelocity and power-velocity relationships (Ripamonti et al 2011). …”
Section: Isokinetic Evaluationmentioning
confidence: 99%
“…However, isokinetic device was not commonly used neither for evaluating low back patient nor for rehabilitation training. A previous study (Ripamonti et al 2011), focusing on torque -velocity and power-velocity relationships determination, showed the interest of determining muscular parameters, such as maximal isometric torque and maximal power, from isokinetic measurements. The purpose of this study was to assess the therapy exercise programme of low back pain patient of the centre de l'Arche.…”
Section: Introductionmentioning
confidence: 99%